2000
DOI: 10.1021/jo991640r
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of N-Heterocyclic Compounds from Cyclopropenethione Derivatives

Abstract: The one-pot reaction of 2-tert-butylthio-3-phenylcyclopropenethione (1a) and its 3-(2-thienyl) derivative (1b) with lithium pyrrolidinide at -70 degrees C, followed by methylation with methyl iodide, gives 6-methylthio-5-phenyl-2,3-dihydro-1H-pyrrolizine (2a) and its 5-(2-thienyl) derivative (2b), respectively. The reaction of 2-tert-butylthio-3-(pyrrolidin-1-yl)cyclopropenethione (1c) with phenyllithium gives also 2a in a high yield under similar conditions, and the reactions of 1a with N-lithium salts of 3-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The reaction of 2-tert-butylthio-3-phenylcyclopropenethione 396 with lithium pyrrolidinide, followed by methylation with methyl iodide, gave the 1Hpyrrolidine derivative 397 (eq 208). 350,351 Similar results have been observed for N-lithium salts of other cyclic amines. Interestingly, the reaction of 2-tertbutylthio-3-(pyrrolidin-1-yl)cyclopropenethione 398 with phenyllithium also gave 397 (eq 209).…”
Section: Ring Expansionsupporting
confidence: 82%
See 3 more Smart Citations
“…The reaction of 2-tert-butylthio-3-phenylcyclopropenethione 396 with lithium pyrrolidinide, followed by methylation with methyl iodide, gave the 1Hpyrrolidine derivative 397 (eq 208). 350,351 Similar results have been observed for N-lithium salts of other cyclic amines. Interestingly, the reaction of 2-tertbutylthio-3-(pyrrolidin-1-yl)cyclopropenethione 398 with phenyllithium also gave 397 (eq 209).…”
Section: Ring Expansionsupporting
confidence: 82%
“…Interestingly, the reaction of 2-tertbutylthio-3-(pyrrolidin-1-yl)cyclopropenethione 398 with phenyllithium also gave 397 (eq 209). 351 Earlier studies indicated that phenylmagnesium bromide attacks diphenylcyclopropenone at the carbonyl carbon (C-1), 36a while phenyllithium attacks the vinylic carbon (C-2). 352 In the latter reaction, a ringopening product, 1,2,2-triphenylpropionic acid, was obtained.…”
Section: Ring Expansionmentioning
confidence: 99%
See 2 more Smart Citations